2009
DOI: 10.1100/tsw.2009.61
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Calypso®4D Localization and Kilovoltage Image Guidance Systems for Interfraction Motion Management of Prostate Patients

Abstract: Prostate cancer represents a model site for advances in understanding inter- and intrafraction motion for radiotherapy. In this study, we examined the correlation of the electromagnetic transponder system/Calypso 4D Localization System with conventional on-board imaging (OBI) using kilovoltage imaging. Initially using a quality assurance (QA) phantom and subsequently using data of seven patients, the vector distances between Calypso- and OBI-recorded shifts were compared using the t-test. For the 30 phantom me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Willoughby et al (16) reported mean and maximum 3D errors of 1.5 mm (SD, 1.1 mm) and 3.8 mm, respectively, over 44 fractions in 11 patients. Ogunleye et al (33) found mean differences of 1.2 mm (SD, 0.9 mm), 1.1 mm (SD, 0.9 mm), and 0.7 mm (SD, 0.5 mm) in the anterior-posterior, superior-inferior, and left-right directions, respectively. Foster et al (34) found mean differences of –0.81 mm (95% LOAs, −2.83 to 2.67 mm), –0.41 mm (95% LOAs, −3.41 to 2.59 mm), and 0.06 mm (95% LOAs, −1.97 to 2.09 mm) for the anterior-posterior, superior-inferior, and left-right directions, respectively, over 250 fractions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Willoughby et al (16) reported mean and maximum 3D errors of 1.5 mm (SD, 1.1 mm) and 3.8 mm, respectively, over 44 fractions in 11 patients. Ogunleye et al (33) found mean differences of 1.2 mm (SD, 0.9 mm), 1.1 mm (SD, 0.9 mm), and 0.7 mm (SD, 0.5 mm) in the anterior-posterior, superior-inferior, and left-right directions, respectively. Foster et al (34) found mean differences of –0.81 mm (95% LOAs, −2.83 to 2.67 mm), –0.41 mm (95% LOAs, −3.41 to 2.59 mm), and 0.06 mm (95% LOAs, −1.97 to 2.09 mm) for the anterior-posterior, superior-inferior, and left-right directions, respectively, over 250 fractions.…”
Section: Discussionmentioning
confidence: 97%
“…The mean and maximum 3D errors were 1.7 mm (SD, 1.0 mm) and 4.6 mm, respectively (18) . Only Calypso interfraction motion estimation validations have been reported 16 , 33 . Willoughby et al (16) reported mean and maximum 3D errors of 1.5 mm (SD, 1.1 mm) and 3.8 mm, respectively, over 44 fractions in 11 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of the Beacons has been verified to millimeter and even submillimeter accuracy both in phantoms and in vivo when compared to X‐ray and CT imaging. ( 13 , 14 ) …”
Section: Methodsmentioning
confidence: 99%
“…Each Beacon in a set of three has a unique frequency response; therefore, each is color coded with its intended position. The accuracy of the Beacons has been verified to millimeter and even submillimeter accuracy both in phantoms and in vivo when compared with x-ray and computed tomography (CT) imaging (12,13).…”
Section: Electromagnetic Beaconsmentioning
confidence: 99%